Analysis of the Effect of Liquidity and Profitability on Financial Performance at PT. Mayora Indah Tbk - Ibrahim Ibrahim; Eldi Eldi; Haeruddin Haeruddin (Syntax Literate, 2023)
This study aims to determine and analyze the effect of liquidity and profitability on financial performance at PT Mayora Indah Tbk. This variable is Liquidity which is proxied by Current Ratio, Profitability which is proxied by Return On Assets (ROA) and financial performance which is proxied by Return On Equity (ROE). Data collection techniques are documentation in the form of financial reports. The data analysis performed was multiple linear regression analysis, classical assumption test and basic statistical test using the SPSS program. Based on the results of the data analysis carried out, the obtained multiple linear equation model Å¶=0.058-0.026X_1+2.235X_2 which means that liquidity partially has a negative and not significant effect on financial performance with a value of 0.249 > 0.05, profitability partially has a positive and significant effect on financial performance with a value of 0.001 <0.05. Simultaneously liquidity and profitability affect financial performance with a value of 0.004 <0.05.